UltraFluoro-guided low-dose caudal anesthesia in patients with ankylosing spondylitis: A case series delineating the technical, safety, and efficacy considerations - Mayank Gupta; Priyanka Gupta; Gegal Pruthi; Hemanth Kumar (Indian Journal of Pain, 2023)
Airway and spine involvement in ankylosing spondylitis (AS) impose unique anesthetic challenges. Ankylosis and intervertebral space obliteration in AS make neuraxial anesthesia technically challenging and sometimes impossible. The anatomical variations of impalpable sacral cornu and complete or partially closed sacral hiatus in adults coupled with positioning difficulties, epidural space narrowing as well as an increased predilection for intraosseous or intravascular injection, and cauda equina syndrome complicate caudal anesthesia in AS. Combined ultrasound and fluoroscopic (ultrafluoro) guidance during caudal anesthesia improves accessibility and identifies and avoids any aberrant nonepidural injection. By providing a fluoroanatomical endpoint, i.e., local anesthetic (LA) contrast washout covering the concordant dermatomes, it reduces the amount of LA required and pressure build-up in already compromised epidural space. Ultrafluoro guidance improves accessibility, identifies, and avoids any nonepidural injection, and reduces the amount of LA required during caudal anesthesia in AS.